Terrestrialisation and the cranial architecture of tetrapods - Ingmar Werneburg (Fossil Record)
Using four extinct land vertebrate species as examples, I discuss ontogenetic strategies as well as the potential influence of bite- and other external forces on the formation of the land vertebrate skull. In principle, areas under biomechanical stress are strongly ossified, whereas regions with little or no stress show only weak or no ossification. In this regard, all plates, arcades and openings of the skull – even in that of the multi-fenestrated dinosaurs – can be explained. I trace the changes in feeding mode and body posture at the transition from semi-aquatic to fully terrestrial tetrapods and discuss changes in the position of bite points. Through evolution, an increasing bite force is argued to have a crucial influence on the formation of new skull openings, such as the supratemporal and the antorbital fenestrae in archosaurs, by changing the direction of stress flows in the skull. The conquest of land was also associated with the appearance of novel types of behaviour such as inter- and intraspecific combats. Horns and other cranial weapons were formed repeatedly, which are shown to alter skull construction when receiving external forces. Changes in the skull biomechanics are associated with body posture and postcranial skeletal anatomy. Additionally, vice versa, the neck muscles are shown to have an important impact on the differentiation of the tetrapod skull. Finally, a new hypothesis is provided for the evolution of the temporal openings, based on biomechanical considerations. I argue that the synapsid (infrafenestral) morphotype was ancestral to amniotes related to a strong anterior bite in the mouth. Along the reptilian lineage – such as in many parareptiles, captorhinids and turtles – temporal fenestration was repeatedly closed by stiffening the temporal region in response to external forces. In addition, I argue that the upper temporal opening evolved first and that the diapsid (bifenestral) morphotype is secondary. The “triapsid” morphotype in ceratopsid dinosaurs is shown to be related to concentrated forces on the animal’s neck frill.